Solve the Sum Equation

Algebra Level 3

The sum of 0 1 2 + 1 2 3 + 2 3 4 + 3 4 5 + + ( x 1 ) x ( x + 1 ) 0 \cdot 1 \cdot 2 + 1 \cdot 2 \cdot 3 + 2 \cdot 3 \cdot 4 + 3 \cdot 4 \cdot 5 + … + (x - 1) \cdot x \cdot (x + 1) is 7292700 7292700 . Find the value of x x .


The answer is 73.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

David Vreken
Dec 5, 2017

The equation can be rewritten in sigma notation as k = 1 x ( k 1 ) k ( k + 1 ) = 7292700 \sum\limits_{k=1}^x (k - 1)k(k + 1) = 7292700 which simplifies to k = 1 x ( k 3 k ) = 7292700 \sum\limits_{k=1}^x (k^3 - k) = 7292700 or k = 1 x k 3 k = 1 x k = 7292700 \sum\limits_{k=1}^x k^3 - \sum\limits_{k=1}^x k = 7292700 . Since the sum of cubes is k = 1 x k 3 = ( x ( x + 1 ) 2 ) 2 \sum\limits_{k=1}^x k^3 = (\frac{x(x+1)}{2})^2 and the sum of integers is k = 1 x k = x ( x + 1 ) 2 \sum\limits_{k=1}^x k = \frac{x(x+1)}{2} , the equation becomes ( x ( x + 1 ) 2 ) 2 x ( x + 1 ) 2 = 7292700 (\frac{x(x+1)}{2})^2 - \frac{x(x+1)}{2} = 7292700 .

Letting u = x ( x + 1 ) 2 u = \frac{x(x+1)}{2} and substituting gives u 2 u = 7292700 u^2 - u = 7292700 and rearranging gives u 2 u 7292700 = 0 u^2 - u - 7292700 = 0 .

Solving this quadratic equation for u u gives u = ( 1 ) ± ( 1 ) 2 4 ( 1 ) ( 7292700 ) 2 ( 1 ) u = \frac{ - (-1) \pm \sqrt {(-1)^2 - 4(1)(-7292700)} }{2(1)} which simplifies to u = 2701 u = 2701 or u = 2700 u = -2700 . Since x > 0 x > 0 according to the original equation’s pattern, u = x ( x + 1 ) 2 > 0 u = \frac{x(x+1)}{2} > 0 , which means u 2700 u \neq -2700 and so u = 2701 u = 2701 .

Since u = x ( x + 1 ) 2 = 2701 u = \frac{x(x+1)}{2} = 2701 , x ( x + 1 ) = 5402 x(x + 1) = 5402 , x 2 + x = 5402 x^2 + x = 5402 , and x 2 + x 5402 = 0 x^2 + x - 5402 = 0 . Solving this quadratic equation for x x gives x = 1 ± 1 2 4 ( 1 ) ( 5402 ) 2 ( 1 ) x = \frac{ - 1 \pm \sqrt {1^2 - 4(1)(-5402)} }{2(1)} which simplifies to x = 73 x = 73 or x = 74 x = -74 . Since x > 0 x > 0 according to the original equation’s pattern, x 74 x \neq -74 and so x = 73 x = 73 .

I used the same pattern, but got lazy and used some trial and error to diverge to 73.

Peter van der Linden - 3 years, 6 months ago

Brilliant problem and solution! It was so fun to solve!

Vinayak Srivastava - 10 months, 4 weeks ago

Log in to reply

This is a bonus test question for a pre-calculus class that I teach. I'm glad you enjoyed it!

David Vreken - 10 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...